Hepatitis B vaccination schedules in genitourinary medicine clinics. Issue 3 (June 1996) - Asboe, D; Rice, P; de Ruiter, A; Bingham, J S
Abstract : OBJECTIVES: To compare two vaccination schedules in delivering hepatitis B vaccine to at-risk genitourinary medicine clinic attenders. SETTING: Genitourinary medicine clinic of St Thomas' Hospital, London, UK. METHODS: Two vaccination protocols were compared. Between January 1991 and December 1992, individuals had doses of recombinant hepatitis B vaccine at 0, 1 and 6 months (standard). From January until October 1993 doses of vaccine were administered at 0, 1 and 2 months (accelerated), following which timing of a booster dose was made on the basis of hepatitis B surface antibody (anti-HBs) assessment. Case notes were reviewed with regard to compliance rates and anti-HBs levels. RESULTS: Two hundred and fourteen individuals were included (standard 104, accelerated 110). Of the standard group 80.8% and 61.5% attended for the 2nd and 3rd doses respectively compared with 80.0% and 75.5% of the accelerated group (attendance for the 3rd dose chi 2 = 4.19, p < 0.05). For both of these groups compliance was significantly better in those who requested vaccination rather than being offered it opportunistically (chi 2 = 4.86, p < 0.05). Seroconversion rates were not significantly different between the two groups (87.5% versus 83.1%). A significantly higher proportion of the standard group, however, achieved anti-HBs levels greater than 100 i.u./l. CONCLUSIONS: Completion of hepatitis B vaccination was improved by changing to a 0, 1 and 2 month protocol. Levels of anti-HBs achieved in the accelerated group, however, were lower. If it is confirmed that maintaining anti-HBs levels is not important in retaining protection against hepatitis B then the accelerated schedule has clear advantage. If not, the advantages may be nullified by the need, in some, for an early booster.